SUDDEN CARDIAC DEATH: ETIOLOGICY IN PATIENTS OF DIFFERENT AGES, RISK FACTORS AND PREVENTION - O. V. Gaisenok (Рациональная фармакотерапия в кардиологии)
Sudden cardiac death etiologicy in different diseases is analyzed as well as its prevalence in different ages, risk factors and prevention.